The Impact of Global Recession on Earnings and Income Inequality in Visegrad Countries - Vašková, Miriama (Comparative Economic Research. Central and Eastern Europe, 2013)
This paper analyses the consequences of the economic downturn for employment, earnings and income inequality in Visegrad countries. It draws on both theoretical and practical evidence of the impact of the recession on earnings and income inequality, as presented in its second part. The third part gives an overview of the development of income inequality in Visegrad countries in the period prior to the global recession. The paper proceeds in its fourth part to a comparative analysis of the empirical data on employment, unemployment, income and income inequality in the Visegrad countries. In its sixth part, the paper summarizes key findings.